MENUJU OTONOMI DAERAH ADIL DAN SEJAHTERA : Revisi Model Otonomi Daerah Menuju Desentralisasi Asimetris - Istania, Ratri; Junaedi, Dedi (Jurnal Desentralisasi, 2012)
Since 1999, Indonesia, after more than 13 years of implementing decentralization political, administrative, and fiscal?programs is still struggling to reach its ultimate goals, which is to bring justice and welfare of the local people. The current implementation of symmetrical decentralized model contains a variety of weaknesses, unable to accommodate principle of efficieny and differences of ethnicities, religions, cultures. One model that can be proposed is asymmetrial decentralization. In this paper, the authors will compare the weaknesses in the past decentralization policy, Law 22/1924 dan 44/1950 to our current policy, Law 32/2004. So far, the findings indicate two problems of symetrical decentralization, which are politics fiscal issues. This paper will utilize national and international publications, as well as any available sources to support the argument. The outline of this paper will divided into five parts, they are as follows: first background; second; concept and definition of decentralization and regional autonomy; third, a review of the symmetrical decentralization versus asymmetrical model; fourth, critical review of the past decentralizion model as a lesson learned; and fifth, a reflection on symmetrical decentralization after 13 year; and the last is ecommendation to implement asymmetrical decentralization.